(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
Drilling mud. A sample of Nigerian clay (Ubakala clay) was used for the project. The clay sample was collected in a raw state, processed and experiments conducted on viscosity which is a very important property of drilling mud. Various concentrations of sodium carbonate were mixed with the clay sample and experiments were conducted to determine the viscosities of the control and the clay-sodium carbonate mixture at periodic time intervals and various speeds of agitation. Response Surface Methodology was used, and with the aid of a MATLAB programming, to study the data obtained from the experiment. The results showed that sodium carbonate concentration, speed of agitation and their various interactions terms and quadratic terms are the significant variables in the statistical model with time being the least significant of the three factors studied. Furthermore, on analysis of the kinetics of the process, a Gaussian model, having the highest values of R2 (50% for Gaussian model, and 25% each for Exponential and Exponential Power models) and the lines of best fit, effectively describes the kinetics of the process and the viscosity of the clay samples in relation to time, concentration of sodium carbonate and speed of agitation. Further work on the Gaussian model gave rise to a new model that can be used to determine the values of the kinetic constants. This new model showed that a speed of agitation between 300rpm and 600rpm gave the best result for the process.